(3GdJHUQI hGdJPcQIs - (3YHO GdQMje Hf GdMSjf Hf YHO GdQMef, CHh GdaVd, Rjf GdOjf, GdMGaX GdYQGbj, J (B806 (3g`s; (3YHO GdQMje Hf GdMSjf Hf YHO GdQMef GdYQGbj, Rjf GdOjf,J (B806 (3g` s ((3GdNGfbGI GdWTJeQjI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi bHd HUMjM GdfjI MSf GdYed hHYO aYde GdMOjK NWjQ hbYg hTQYJ ai TQM deG HSWJg hChVMJg s
(3BNQgG (B:s
(3aef gh ef Cgd OGQjG eKdG dg Cf jbhd ai fSHg GdOGQi hGdOeTbi hGdTGei aEf CQGO GdLeY HjfgeG adjHOC HGdGYe ajbhd GdTGei GdOeTbi GdOGQi s
(3GdfSNI HgG MhGTs
(3HgG HYV GdUaMGJ UhQJ YdjgG eNWhW BNQ ELGRI GdeDda dcd ef SeY efg GdEQLhRI GdePchQI ChH HYVgG Cf jQhi LejY gPG GdTQM YdjgGs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B344s
Keywords: (3GdMOjK h GdeUWdMs